Pengaruh Budaya Organisasi, Kualitas Sumber Daya Manusia Dan Disiplin Terhadap Kinerja Karyawan (Studi Kasus Pada Pt. Ledokombo Jember) - Nova Ade Fajar Wijaya; Hadi Sunaryo; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2020)
Abstract This study aims to determine the effect of organizational culture, quality of human resources and discipline on the performance of employees of PT. Ledokombo Jember. The population in this study were employees of PT. Ledokombo Jember. The sampling technique used in this study is saturated sampling technique. The population in this study was less than 100 people. The number of samples in this study were all members of 65 people. The results showed that the variables of organizational culture, quality of human resources and discipline had a good relationship to improve the performance of the employees of PT. Ledokombo jember. The known value of F> F table and significance> 0.05, shows that there is a direct and significant impact of organizational culture on employee performance and discipline. In adition there are also indirect impacts on the quality of human resources on employee performance. Employee performance will increase in PT. Ledokombo Jember. Keywords: Organizational Culture, Quality of Human Resources, Discipline and Employee Performance